VARIASI MORFOLOGI LIMA POPULASI Meretrix spp. (Bivalvia:Veneridae) DI INDONES - Akhmadi, Mohammad Fadnan; Trijoko, Trijoko (Jurnal Harpodon Borneo, 2016)
Information on morphological characters is very important to know because it became the basis for the conventional cross-breeding to obtain superior quality seeds. Sampling was done by using Purposive Random Sampling at five stations namely Kota Tarakan, Ketapang, Takalar, Trenggalek and Demak. Based on the results Meretrix spp. as many as 84 individuals were grouped into 12 variations of hues. Specimens obtained grouped into three species, namely M. meretrix has the characteristics of a thick shell structure, strong and shiny. The size of the inner shells posterior margin is longer than the anterior margin. Margin dorsoposterior flat and angle ventroposterior form a triangle. Dorsoanterior margin slightly concave and ventroanterior corner in a half ellipse; Meretrix lusoria have characteristics size inner shells posterior margin is longer than the anterior margin. Margin dorsoposterior flat and angle ventroposterior form a triangle. Dorsoanterior margin slightly concave and ventroanterior corner in a half ellipse; Meretrix sp. has characteristics similar to M. meretrix overall but there are differences that have color variations on the internal shell (black-purple), it is different with the character of the Genus Meretrix Keywords : Meretrix meretrix, Meretrix lusoria, Clams Morphological.